2012
DOI: 10.1007/s10532-012-9584-3
|View full text |Cite
|
Sign up to set email alerts
|

Fungal biodegradation of phthalate plasticizer in situ

Abstract: This unique study describes how Aspergillus japonicus, Penicillium brocae and Purpureocillium lilacinum, three novel isolates of our laboratory from heavily plastics-contaminated soil completely utilized the plasticizer di(2-ethylhexyl)phthalate (DEHP) bound to PVC blood storage bags (BB) in simple basal salt medium (BSM) by static submerged growth (28 °C). Initial quantification as well as percentage utilization of DEHP blended to BB were estimated periodically by extracting it into n-hexane. A two-stage cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Luo et al (2009) studied the degradability of the three dimethyl phthalate isomer esters (DMPEs) by a Fusarium species isolated from mangrove sediment. Pradeep et al (2013) reported the complete degradation of the plasticizer di(2-ethylhexyl)phthalate (DEHP) bound to PVC blood storage bags (BB) in simple basal salt medium (BSM) by Aspergillus japonicus, Penicillium brocae and Purpureocillium lilacinum, isolated from heavily plastics-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al (2009) studied the degradability of the three dimethyl phthalate isomer esters (DMPEs) by a Fusarium species isolated from mangrove sediment. Pradeep et al (2013) reported the complete degradation of the plasticizer di(2-ethylhexyl)phthalate (DEHP) bound to PVC blood storage bags (BB) in simple basal salt medium (BSM) by Aspergillus japonicus, Penicillium brocae and Purpureocillium lilacinum, isolated from heavily plastics-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…HQ645935; MTCC No. 5710, a patent deposit from our laboratory), isolated from heavily plastics polluted sewage sludge collected from the Canoly Canal; flowing through Kozhikode City, Kerala, India (11.2500 N;75.7667 E) was cultured in a simple BSM containing (g/L) K 2 HPO 4 , 1.0; NaCl, 1.0; NH 4 Cl, 0.5 and MgSO 4 , 0.4 (initial pH, 7.2; and supplemented with DEHP blended) (in situ cultivation) BB Pradeep et al, 2013). Commercially available HL haemopack BB (Batch No.…”
Section: Organism and Growth Conditionsmentioning
confidence: 99%
“…We for the first time demonstrated that the mycelial fungi can efficiently degrade DEHP blended in a commercial PVC plastics in situ, i.e., blood bag (BB) Pradeep et al, 2013). Many bacteria are also known to degrade various phthalates (Liang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phthalates or esters of phthalic acid are a class of xenobiotic organic compounds widely employed to make plastic goods more flexible. Some of the commonly used phthalates are described in Table 1 [2,3], which are not chemically bound to the polymer mesh, and hence, they would easily migrate from plastic products into the surrounding environments [4][5][6]. Many experimental studies (in silico, in vitro mechanistic, pre-clinical and clinical) have shown that phthalates act as endocrine disruptors in vivo, apart from causing various health problems including hepatomegaly, osteoporosis, peroxisome proliferation, feminization of boys, reduction in body weight, skin and breast cancers, etc.…”
Section: Introductionmentioning
confidence: 99%